Sosialisasi Dan Pelaksanaan Pemanfaatan Canva Sebagai Persiapan Siswa SMK Negeri 1 Tebo Dalam Memasuki Dunia Pekerjaan - Indriani Harianja, Sri; Sapira, Dea; Eristian, Anisya; Zulfani, Adzra; Siregar, Masyunita (Pendidikan Sejarah FKIP Universitas JAMBI, 2024)
The Teaching Campus Program is one of the programs planned by the Ministry of Education to improve student abilities and numeracy literacy skills in students who are still in the school environment. The Teaching Campus Program is a form of implementing Merdeka-Learning-Free Campus-Independence (MBKM) in the form of teaching activities, technology adaptation, and administration by empowering students to help with the learning process in school institutions. One of them is at SMKN 1 Tebo which is located on Jalan Lintas Tebo Bungo KM.08, Tebo District/Regency, Jambi. The scope of campus teaching implementation focuses on students' numeracy literacy skills and digital technology by compiling and planning programs based on problem findings in schools. It is hoped that this program will be a solution for schools in the areas of understanding literacy and numeracy and introducing various digital applications that are really needed by students through the introduction of Canva. An introduction to Canva provides new understanding and knowledge thereby preparing students to enter the workforce. This program is expected to have a positive impact on teachers and students on students' interest, motivation, creativity and imagination, especially regarding digital technology. Apart from having an impact on the school, this program provides opportunities for students to carry out activities that are closely related to quality teaching and learning processes